Quality of life and psychological well-being in parents of children diagnosed autism spectrum disorder from the Center for neurological development Communicates in the city of Cochabamba-Bolivia - Julian Mendoza, Betzabe Mariela (2024)
The objective of this research is to identify the relationship between quality of life and the psychological well-being of parents of children diagnosed with autism spectrum disorder or its acronym ASD from the Comprehensive Center for Neurological Development (CIDN) Comunica, in the department of Cochabamba, The study corresponds to a correlational descriptive research with a quantitative approach. Based on the management of the data, this research corresponds to a non-experimental design, the population selected for the research is made up of 22 parents, who have children diagnosed with autism spectrum disorder who attend sequentially the CIDN in the city of Cochabamba. The technique used for the collection of data and information was the application of surveys in which two duly validated questionnaires were used as instruments (Psychological well-being scale developed by Ryff from its 6 dimensions and the family quality of life scale elaborated by Verdugo, Sainz and Rodríguez), taking as a population 22 parents of children with autism from the Comunica Comprehensive Neurological Center. who agreed to be part of this The results obtained regarding psychological well-being are within a moderate category and in terms of quality of family life, a moderately high percentage is observed. With respect to the correlations of each dimension, positive correlations were obtained in all the dimensions of psychological well-being, And regarding the correlation between the two variables of quality of family life and psychological well-being, a result of moderate positive correlation was obtained, based on this it was concluded that there is a correlation between the two variables of psychological well-being and quality of family life.